THE USE OF CREATIVE AND EDUCATIONAL GAMES IN THE FORMATION OF SOCIO-LEGAL COMPETENCES OF STUDENTS IN THE LESSONS OF THE PRIMARY CLASS - Khakimova, Nargiza Supkhanovna (Educational Research in Universal Sciences, 2023)
Creative and educational games and familiarization with them in the formation of social and legal competencies in primary school. This article discusses the importance of creative and educational play in the formation of social and legal competencies of the game in the classroom of students in their lives and the significance of its development at the younger stages and the formation of its use.